2020
DOI: 10.1109/jsen.2020.2983933
|View full text |Cite
|
Sign up to set email alerts
|

Application and Evaluation of Lighthouse Technology for Precision Motion Capture

Abstract: Without his patience, guidance, and support this work would not have been possible. I am also grateful to FTL Labs Corp. for their assistance and sponsorship for the project. A big thanks to Damon and Jared from FTL Labs for developing a graphical user interface that aided the thesis work. To my committee members, Andrew LaPrè and Yossi Chait, I am extremely thankful for all the suggestions, critiques and feedback which have played a really important role in shaping the thesis. Last but not the least, I also w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…They concluded that the Vive system has the potential for tracking valid and reliable kinematic data. In [ 17 ] the authors studied the performance of lighthouse technology, which is also used in the Vive system, for applications in biomechanics and robotics. They mounted a tracker on a robot end-effector and compared the poses of the motion trackers with the poses obtained by the end-effector.…”
Section: Related Workmentioning
confidence: 99%
“…They concluded that the Vive system has the potential for tracking valid and reliable kinematic data. In [ 17 ] the authors studied the performance of lighthouse technology, which is also used in the Vive system, for applications in biomechanics and robotics. They mounted a tracker on a robot end-effector and compared the poses of the motion trackers with the poses obtained by the end-effector.…”
Section: Related Workmentioning
confidence: 99%
“…To this end, it is necessary to find a demonstration platform suitable to obtain the human operators' 3C product assembly motions, i.e. finding a suitable motion capture technique [8] [9]. As the 3C product assembly motions involve complicated motions of fingers and bimanual collaboration, the optical motion capture sensors, which have been included in studies of LfD for assembly applications [10]- [14], provides an effective way to record the workers' 3C product assembly motions [15].…”
Section: Introductionmentioning
confidence: 99%
“…Several researches that assessed 3-D pose estimation of the lighthouse localization system have been conducted [9], [13]- [25]. Niehorster et al [14] firstly conducted experiments with the lighthouse system and announced the results about its accuracy, jitter, and latency.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that a sufficient care must be taken to use the system for general research purpose because the lighthouse system has a systemic error of a slanted ground problem. Sitole et al [25] solved the systemic error problem raised by Niehorster et al using an additional tracked object as a global tracking frame. Groves et al [20] conducted experiments using the second generation lighthouse system, commercial optical tracking system, and a hybrid system that combined former two systems for a medical application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation